Infection prevention and control training and capacity building during the Ebola epidemic in Guinea - Soeters, Heidi M.; Koivogui, Lamine; de Beer, Lindsey; Johnson, Candice Y.; Diaby, Dianka; Ouedraogo, Abdoulaye; Touré, Fatoumata; Bangoura, Fodé Ousmane; Chang, Michelle A.; Chea, Nora; Dotson, Ellen M.; Finlay, Alyssa; et al. (PLOS ONE, 2018)
Background During the 2014–2016 Ebola epidemic in West Africa, a key epidemiological feature was disease transmission within healthcare facilities, indicating a need for infection prevention and control (IPC) training and support. Methods IPC training was provided to frontline healthcare workers (HCW) in healthcare facilities that were not Ebola treatment units, as well as to IPC trainers and IPC supervisors placed in healthcare facilities. Trainings included both didactic and hands-on components, and were assessed using pre-tests, post-tests and practical evaluations. We calculated median percent increase in knowledge. Results From October–December 2014, 20 IPC courses trained 1,625 Guineans: 1,521 HCW, 55 IPC trainers, and 49 IPC supervisors. Median test scores increased 40% (interquartile range [IQR]: 19–86%) among HCW, 15% (IQR: 8–33%) among IPC trainers, and 21% (IQR: 15–30%) among IPC supervisors (all P<0.0001) to post-test scores of 83%, 93%, and 93%, respectively. Conclusions IPC training resulted in clear improvements in knowledge and was feasible in a public health emergency setting. This method of IPC training addressed a high demand among HCW. Valuable lessons were learned to facilitate expansion of IPC training to other prefectures; this model may be considered when responding to other large outbreaks.